Cadmium Adsorption Capacity on Inceptisols Brebes and its Uptake by Shallot as Plant Indicator - LADY R. WIDOWATI; L.I NURHAYATI; . CHARLENA; S. SRI DWININGSIH; J. SRI ADININGSIH (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2003)
A research had been done in the laboratory and greenhouse of the Indonesian Center for Soil and Agroclimate Research and Developmant to study cadmium adsorption capacity, availability, and its uptake by shallot as plant indicator in order to antisipate Cd pollution in soil and plant in the future. The steps of the research were adsorption study in the laboratoryand followed by greenhouse trial. Cadmium adsorption study was using the rate of 0; 10; 30; 40; 50; 60; 70; 80; 90; and 100 ppm. The trial on response and plant uptake on cadmium used 2 kg soil pot-1 then planted with shallot var. Bima for 2 months. The experiment utilized completely randomized design with six treatments and three replicates. The rates of Cd were 0; 25; 50; 100; 200; and 400 ppm Cd (Cd(NO3)2). The results showed that Inceptisols Brebes adsorption, maximum adsorption, andbuffering capacity are 14.78 ml μg-1; 879 μg g-1 and 12,987 ml μg-1, respectively. The cadmium availability in the soil could be calculated by using the equation: Cdexchangeable = 0.0532(Cdapplied) – 1.6757, r2 = 0.9686 (after treatment); Cdexchangeable = 0.0671(Cdapplied) + 0.924, r2 = 0.9903 (after harvest). Application of 50 ppm Cd reduced shallot production up to 31% significant with total uptake of 4.57 ppm Cd. The Cd uptake increased significantly for treatment 25 ppm, Cd in shallot tuber(2.36 mg Cd per kg dry weight), and at 200 ppm Cd in leaves (7.16 mg kg-1). The cadmium content in tuber at treatment 2 ppm Cd (2.36 ppm Cd) exceeds critical value/permissible limit of vegetable for consumption.